Quantum Dot Devices 2012
DOI: 10.1007/978-1-4614-3570-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Optically Injected Single-Mode Quantum Dot Lasers

Abstract: The response of an optically injected quantum dot semiconductor laser is studied both experimentally and theoretically. Specifically, the locking boundaries are investigated, revealing features more commonly associated with Class A lasers rather than conventional Class B semiconductor lasers (SLs). Further, various dynamical regimes are observed including excitability and multistability. Of particular interest is the observation of a phase-locked bistability. We determine the stability diagram analytically usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…[21][22][23][24] However, the study of OB and NS in nanostructure lasers has not yet attracted much attention despite their theoretically superior properties. Devices made using advanced QDot or QDash active regions offer many potential advantages including ultrafast carrier dynamics, 25 reduced linewidth enhancement factor (a), 26 and low temperature dependence of the threshold current.…”
mentioning
confidence: 99%
“…[21][22][23][24] However, the study of OB and NS in nanostructure lasers has not yet attracted much attention despite their theoretically superior properties. Devices made using advanced QDot or QDash active regions offer many potential advantages including ultrafast carrier dynamics, 25 reduced linewidth enhancement factor (a), 26 and low temperature dependence of the threshold current.…”
mentioning
confidence: 99%
“…The stability diagram of an injected QC laser bears striking analogies with the one of a QD laser when the latter admits strongly damped relaxation oscillations [6,7]. However, the values of the parameters appearing in the rate equations for QD lasers are not as well documented as for QC lasers.…”
Section: Discussionmentioning
confidence: 99%
“…Motivated by recent work on injected locked quantum dot lasers [6,7], Eqs. (18)- (20) were recently analyzed by Kelleher et al [24] We now propose to analyze the linear stability of the steady state.…”
Section: Fast Escape Of Carriers At the Lower Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of such devices while emitting from the GS only has been well investigated in recent years and studies of the behavior under optical injection have revealed many interesting phenomena. [1][2][3] While studies of optically injected QD lasers in the two-state or the ES only regimes are much more rare, interest in these regimes has recently grown. Of note for this work is the ultrafast all-optical switching between the GS and ES obtained in.…”
Section: Introductionmentioning
confidence: 99%